2020
DOI: 10.1515/hsz-2020-0195
|View full text |Cite
|
Sign up to set email alerts
|

Individual and combined effects of GIP and xenin on differentiation, glucose uptake and lipolysis in 3T3-L1 adipocytes

Abstract: The incretin hormone glucose-dependent insulinotropic polypeptide (GIP), released postprandially from K-cells, has established actions on adipocytes and lipid metabolism. In addition, xenin, a related peptide hormone also secreted from K-cells after a meal, has postulated effects on energy regulation and lipid turnover. The current study has probed direct individual and combined effects of GIP and xenin on adipocyte function in 3T3-L1 adipocytes, using enzyme-resistant peptide analogues, (D-Ala2)GIP and xenin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…However, activation of all three hormone signalling pathways appears to lead to reduced lipid deposition. In some agreement, interaction between xenin and GIP pathways within adipocytes has previously been noted to induce responses that contrast with effects of either hormone alone [ 46 ].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…However, activation of all three hormone signalling pathways appears to lead to reduced lipid deposition. In some agreement, interaction between xenin and GIP pathways within adipocytes has previously been noted to induce responses that contrast with effects of either hormone alone [ 46 ].…”
Section: Discussionmentioning
confidence: 79%
“…In agreement, whilst circulating lipid profile of HFF mice was improved by all treatment regimens, only combined therapy reduced triacylglycerol concentrations. In this regard, originally it was believed that xenin acts on adipose tissue to stimulate lipolysis [ 45 ], but more recent studies reveal direct lipogenic and adipocyte differentiation actions of xenin [ 46 ]. In agreement, an elegant study has suggested that neurotensin can also promote lipid accumulation [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“… 32 There was an original hypothesis that xenin acts on adipose tissue to stimulate lipolysis, and that xenin may hold promise as an anti-obesity therapy by reducing adipose fat depots, but such observations were somewhat inconsistent. 32 Thus, English et al 33 recently revealed direct lipogenic and lipolytic actions of xenin in 3T3-L1 adipocytes, whilst also promoting adipocyte differentiation in 3T3-L1 pre-adipocytes, through alterations in gene expression of LPL and FASN, key promoters of 3T3-L1 differentiation. 33 The effects of xenin to positively modulate lipolysis, lipogenesis and adipocyte differentiation are likely modulated through NTRS1 activation on the AKT/PI3K pathway.…”
Section: Function Potential Mechanism Of Action and Therapeutic Application Of Xeninmentioning
confidence: 99%
“… 32 Thus, English et al 33 recently revealed direct lipogenic and lipolytic actions of xenin in 3T3-L1 adipocytes, whilst also promoting adipocyte differentiation in 3T3-L1 pre-adipocytes, through alterations in gene expression of LPL and FASN, key promoters of 3T3-L1 differentiation. 33 The effects of xenin to positively modulate lipolysis, lipogenesis and adipocyte differentiation are likely modulated through NTRS1 activation on the AKT/PI3K pathway. 33 However, it should be noted that the actions of xenin on lipid metabolism are still not well defined and require more detailed study, especially in light of some conflicting observations.…”
Section: Function Potential Mechanism Of Action and Therapeutic Application Of Xeninmentioning
confidence: 99%
See 1 more Smart Citation